Characteristics of Hyperglycemic Crises in An Adult Population in a Teaching Hospital in Colombia (2018)
ABSTRACT: Background: Hyperglycemic crisis are the most serious forms of acute decompensation of diabetes mellitus and require urgent medical attention. The epidemiological data of these conditions in Latin America are scarce and in Colombia unknown, that is why we decided to describe the clinical characteristics and factors associated with the mortality of adults who presented with hyperglycemic crises in a teaching hospital in Colombia. Materials and methods: Retrospective cohort study of all episodes of hyperglycemic crisis treated in Pablo Tobón Uribe Hospital in a three-year period. Results: The records of 2233 hospitalization episodes related to diabetes mellitus were review, the prevalence of hyperglycemic crises was 2%, half of the events were diabetic ketoacidosis and 57% of the events occurred in people with type 2 diabetes mellitus, 32% of the events were precipitated by an infection and 27% by and inadequate therapy. The average hospital length of stay was 14 ± 3 days and the mortality rate 2.27%. Conclusions: In a teaching hospital in Latin America hyperglycemic crises are common, with diabetic ketoacidosis being the most frequent, and in a significant number of cases may be preventable. The hospital length of stay in our population is longer than reported in the literature.